Kajian Semiotika Dalam Buku Antologi Puisi Berjudul Museum Penghancur Dokumen Karya Afrizal Malna: A Semiotic Study in the Poetry Anthology Museum Penghancur Dokumen by Afrizal Malna - Jania Ningsih; Ridia Juwita Dewi; Muthia Rafli; Fajri Winanda; Elmustian Elmustian (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to analyze the signs and meanings in the poetry anthology Museum Penghancur Dokumen by Afrizal Malna using Roland Barthes' semiotic theory. Frizal Malna is a poet known for his writing style, which often uses everyday objects as symbols to express social and human realities. This study uses a qualitative descriptive method with a literature review approach. The research data consists of the text of the poetry anthology, which is analyzed through three levels of meaning: denotative, connotative, and mythical. The results of the analysis show that at the denotative level, these poems use various simple objects that are familiar in everyday life, such as erasers, glue, scissors, rulers, and paper. At the connotative level, these objects become symbols of loss, alienation, social wounds, and emptiness in modern life. Meanwhile, at the mythical level, this poem forms a grand narrative about humans who are often trapped in social systems and the Indonesian nation that has not yet completely escaped the shadow of colonialism. Thus, this work presents social criticism and deep reflection on the condition of modern humans.